2006
DOI: 10.1016/j.jacc.2005.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Coronary Microvascular Flow Impairment to Long-Term Remodeling and Systolic Dysfunction in Hypertrophic Cardiomyopathy

Abstract: Severe microvascular dysfunction is a potent long-term predictor of adverse LV remodeling and systolic dysfunction in HCM. Our findings indicate microvascular dysfunction as a potential target for prevention of disease progression and heart failure in HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 22 publications
6
143
0
3
Order By: Relevance
“…Użycie głowicy przezprzełykowej z kolei ułatwia ciągły udział w procedurze i zapewnia dobrą jakość badania, ale wymaga zastosowania znieczulenia ogólnego. Pomiaru gradientu w LVOT można dokonać z projekcji przezżołądkowej koniuszkowej czterojamowej (0 o ) oraz środkowoprzełykowej w osi długiej na poziomie zastawki aortalnej (120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130) o ). Należy pamiętać, że zmierzony gradient w LVOT może być zaniżony z powodu sedacji ogólnej.…”
Section: Powiększenie Lewego Przedsionkaunclassified
See 1 more Smart Citation
“…Użycie głowicy przezprzełykowej z kolei ułatwia ciągły udział w procedurze i zapewnia dobrą jakość badania, ale wymaga zastosowania znieczulenia ogólnego. Pomiaru gradientu w LVOT można dokonać z projekcji przezżołądkowej koniuszkowej czterojamowej (0 o ) oraz środkowoprzełykowej w osi długiej na poziomie zastawki aortalnej (120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130) o ). Należy pamiętać, że zmierzony gradient w LVOT może być zaniżony z powodu sedacji ogólnej.…”
Section: Powiększenie Lewego Przedsionkaunclassified
“…Do końca nie ma jasności co do znaczenia klinicznego mostków mięśniowych, dość często spotykanych nad tętnicą zstępującą przednią [88]. Ocena niedokrwienia, zazwyczaj indukowanego wysiłkiem, jest istotna u pacjentów z HCM ze względu na jego znaczenie prognostyczne (związek z potencjalnie letalnymi arytmiami i niekorzystną przebudową serca: rozstrzeń, jawna dysfunkcja skurczowa [121,126]. Metody radioizotopowe, takie jak SPECT (Thallium-201, 99mTc) czy PET (N-amoniak) z powodzeniem są wykorzystywane w ocenie zaburzeń perfuzji mięśnia sercowego wywołanych wysiłkiem czy wazodylatacją (dipiridamol, adenozyna) [122,123,127,128].…”
Section: Obrazowanie Radioizotopoweunclassified
“…11 We did not measure baseline MBF in order to minimize patient exposure, taking into account that previous studies demonstrate that this parameter is not significantly different between HCM patients and healthy controls 4 and that hMBF is superior to coronary flow reserve in predicting LV remodeling and outcome in HCM patients. 8,9 All studies were analyzed by expert observers, completely unaware of the patient clinical and echocardiographic data.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…4,5 CMD has been identified as a powerful predictor of adverse outcome due to heart failure progression and death in HCM patients. [6][7][8][9] To date, it is unknown whether AF and CMD are associated, and whether the clinical consequences of CMD may be partly mediated by increased susceptibility to arrhythmia. Thus, the aim of the present study was to explore the possible relationship between these two unfavorable features in a large HCM patient cohort studied by PET.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Recent studies have shown that severe impairment of the coronary vasodilator response to dipyridamole is strongly associated with 'end stage' disease, long-term clinical deterioration and cardiac death in patients with HCM. 7,8 A number of mechanisms are associated with the decrease in CFR, including diastolic dysfunction, 9,10 systolic compression of the septal coronary branches, 11,12 the existence and degree of LV outflow tract gradient, 13 small-vessel disease of the intramyocardial arterioles [14][15][16] and inadequate capillary density relative to the increase in myocardial mass. 17 Although all mechanisms have a role in creating an imbalance between oxygen supply and demand, their relative contribution to the decrease in CFR has not yet been evaluated in HCM patients.…”
mentioning
confidence: 99%